Análisis de ciclo de vida del producto empaque sello cuñete Aro de la empresa Almaplast S.A.S (2024)
The use of massive plastic has led to considerable figures for its regular use, within the companies generating plastic products there is a responsibility on the consequences that are involved from the production process, as a way to influence organizations and that they can know about these impacts, the life cycle analysis is presented as an alternative that brings various benefits and advantages under the phases stipulated by the ISO 14040 standard which is based on the framework to meet an LCA is why the company Almaplast S.A. S, seeks to learn about the different environmental aspects that are influencing after the generation of the product called “seal packaging for wedge” based on this, a method was used through the Open LCA program where it was possible to understand and understand the environmental impact assessment from the ReCiPe midpoint/endpoint methodology and EF method for the characterization of environmental impacts, This will allow us to understand which are those impacts to be considered within the 3 main indicators and understand why they are being generated in the production process, this will give knowledge to the company about the environmental impacts affected and also be able to provide various alternatives which can be implemented in the company and can have a mitigation against the impacts generated from acceptable alternatives for the company